1995
DOI: 10.1183/09031936.95.08020230
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the GABA agonist, baclofen, on sleep and breathing

Abstract: We therefore conducted a double-blind, placebo-controlled, cross-over study of baclofen 25 mg, administered before sleep in 10 snorers with mild sleep-disordered breathing (respiratory disturbance index <30 events per sleep hour). Each subject underwent two standard polysomnographic assessments, one week apart.Total sleep time was significantly prolonged by baclofen (placebo 356±9.9 SEM min; baclofen 386±9.9 min). Both nonrapid eye movement(REM) and REM sleep duration were increased (nonREM: placebo 295±6.8 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
2
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 16 publications
1
42
2
3
Order By: Relevance
“…It has been shown that a single dose of 25 mg baclofen alters the sleep architecture and produces a small reduction in mean sleep oxygen saturation although it does not signi®cantly increase sleep-disordered breathing. 33 Thus, baclofen might be a risk factor for OSA but our data indicates that moderate doses are not a major risk factor.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…It has been shown that a single dose of 25 mg baclofen alters the sleep architecture and produces a small reduction in mean sleep oxygen saturation although it does not signi®cantly increase sleep-disordered breathing. 33 Thus, baclofen might be a risk factor for OSA but our data indicates that moderate doses are not a major risk factor.…”
Section: Discussionmentioning
confidence: 61%
“…However, the majority 22,33 of the tetraplegic subjects in the present study had difficulties in changing sleeping position during the night and thus spent all night in the supine position. Previous studies of non-injured subjects indicate that the supine position increases the risk for OSA 31 while the lateral position reduces the risk.…”
Section: Discussionmentioning
confidence: 73%
“…GABA A receptor activation is well known to induce sleep-promoting responses (26). Administration of the GABA B agonist baclofen (25 mg) before sleep in a clinical study also significantly prolonged total sleep time and reduced the time spent awake after sleep onset (27). On the other hand, the GABA B antagonist CGP35348 increased the duration of both non-REM and REM sleep in aged rats compared to those in saline-injected controls when injected during the night (28) and decreased non-REM sleep while increasing the duration of waking and REM sleep when injected during the day (29).…”
Section: Discussionmentioning
confidence: 99%
“…Spasmolytic medication in itself may compromise the sleep. 55 Another major issue disturbing sleep among SCI individuals was di culty with voiding. For those with suprasacral lesions using re¯ex-voiding by tapping, bladder distension with autonomic dysre¯exia may be one reason for waking during the night.…”
Section: Discussionmentioning
confidence: 99%